The cemetery as a part of the geography of tourism - Tanaś, Sławoj (Turyzm/Tourism, 2004)
The article reviews research into the tourism resource of cemeteries and establishes the place they oc-cupy in geographical and tourism space. At the same time the author discusses attitudes to ‘cemetery space’ of interest from a tourism perspective. The review is based on the literature and the author’s study of the tourism resources of cemeteries such as those from World War I in the Beskid Niski range of hills.